'Practicing' Cosmopolitanism in Knowledge Spaces, Cityscapes and Marketplaces. (October 2015) - Mukherjee, Payel Chattopadhyay; Rath, Arnapurna
In this article, we observe the possibility of 'practicing' cosmopolitanism in three distinct experiential spaces intrinsic to human existence: knowledge spaces, habitation spaces and marketplaces. Although cosmopolitanism has been overwhelmingly deliberated upon across multiple disciplines, it has been confined to 'conceptualisms' in the Western scholarship. On the other hand, we find that some of the works of thinkers, such as, Rabindranath Tagore's Creative Unity (1922), Aurobindo Ghosh's The Ideal of Human Unity (1915–1918) and Mikhail Bakhtin's Rabelais and His World (1984), open the possibilities of experiencing cosmopolitanism in lived human spaces. Cosmopolitanism emerges through knowledge generation and exchanges in the academic vision of Tagore's ideal Visva-Bharati, in the everydayness of city life through Aurobindo's Auroville and in the cultural spaces of the Bakhtinian marketplace. Further, we find that cosmopolitanism in these thinkers interweaves the physical place with spaces of the mind. The individual emerges as a core of their cosmopolitan worldview. We argue that these thinkers not only pave the way for recognizing cosmopolitanism in real, lived spaces but also inspire a future vision, practicable in the society through academic institutions, human habitats and regular interactions at marketplaces.